Bridging the gap between decision-making and emerging big data sources: an application of a model-based framework to disaster management in Brazil - Horita, Flávio E. A.; Albuquerque, João Porto de (Decision support systems, 2017)
With the emergence of big data and new data sources, a challenge posed to today's organizations consists of identifying how to align their decision-making and organizational processes to data that could help them make better-informed decisions. This paper presents a study in the context of disaster management in Brazil that applies oDMN+, a framework that connects decision-making with data sources through an extended modeling notation and a modeling process. The study results revealed that the framework is an effective approach for improving the understanding of how to leverage big data in the organization's decision-making.
Gesehen am 04.09.2018